2008
DOI: 10.1007/s11605-007-0310-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Recurrence of Small Hepatocellular Carcinoma after Hepatic Resection or Microwave Ablation: A Retrospective Study

Abstract: The metastasis and recurrence rate after MA is similar to that after HR, and the methods of therapy do not affect the prognosis of small HCC. The metastasis and recurrence of patients with small HCC will differ depending on tumor differentiation, expressions of VEGF and c-Met in HCC tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 31 publications
4
76
1
1
Order By: Relevance
“…Many studies have reported on the association between alterations in MET and poor prognosis and/or disease severity in human cancers (25)(26)(27)(28). These findings support the hypothesis that specific alterations in MET may provide predictive capacity for identifying patients most likely to benefit from MET inhibitor therapy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Many studies have reported on the association between alterations in MET and poor prognosis and/or disease severity in human cancers (25)(26)(27)(28). These findings support the hypothesis that specific alterations in MET may provide predictive capacity for identifying patients most likely to benefit from MET inhibitor therapy.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, the HGF/MET signaling pathway has been shown to be activated during the genesis and progression of hepatocellular carcinoma. Many reports have highlighted the prevalence of MET gene and protein expression in hepatocellular carcinoma, and have investigated the role of MET signaling in hepatocellular carcinoma progression and maintenance (24)(25)(26)(27)(28). The importance of MET signaling in these processes suggests that the status of MET gene amplification and/or protein expression in patients with hepatocellular carcinoma may serve as potential biomarkers for prognosis or response to anti-HGF/MET therapy.…”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, other studies have shown that expression of VEGF in HCC was correlated with the probability of recurrence after tumor resection or ablation. [43][44][45][46] Collectively, these findings suggest that tissue VEGF expression in HCC may indicate more advanced disease and reduced median survival. However, these studies had relatively small patient numbers and used different VEGF detection assays.…”
Section: Molecular Interactions With Vegfmentioning
confidence: 92%
“…[4][5][6] However, the long-term survival of patients with HCC remains unsatisfactory because of the high incidence of recurrence and metastasis after hepatic resection, with a 5-year survival rate of 20% to 30% reported in the literature. 7,8 To predict recurrence, metastasis, and prognosis in patients with HCC after hepatic resection is a significant clinical issue. Although the identification of many prognostic markers of HCC, such as vascular endothelial growth factor, osteopontin, and transforming growth factor-b, resulted from extensive clinical as well as basic research efforts, the available markers still are not able to accurately predict the survival of patients with HCC.…”
mentioning
confidence: 99%